Pelatihan Kepemimpinan terhadap Kepuasan Kerja dan Kemampuan Manajerial Kepala Ruang - Gryttha Tondang; Jenny Marlindawani Purba; Arlina Nurbaity Lubis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the relationship between leadership training and job satisfaction of the head of space. This research method is quantitative research with a comparative causal design. The results showed that the majority of work before being given the leadership training intervention in the intervention group and the control group was low, namely 27 respondents (100%) in the intervention group with an average value of 50.07 and 27 respondents (100%) in the control group with an average value of 61, 11. Job satisfaction after being given the leadership training intervention in the high majority intervention group, namely 16 respondents (59.3%) with an average value of 72.30 pleasure, while without providing leadership training intervention in the low majority control group, namely 27 respondents with an average value of 61, 33 %. Based on the Wilcoxon Signed-Rank statistical test with significant job satisfaction (Z=-4.552, p=0.000). In short, there is an effect of leadership training on the job satisfaction of the head of space. Keywords: Leadership, Job Satisfaction, Training